Effects of low-dose sodium nitrite on the structure of yak meat myoglobin during wet curing - Guoyuan Ma; Zhuo Wang; Qunli Yu; Ling Han; Cheng Chen; Zhaobin Guo (Food Chemistry: X, 2022)
The effects of low doses of sodium nitrite on yak meat colouring, myoglobin oxygenation status, myoglobin aggregation and myoglobin structure were evaluated using Fourier transform infrared spectroscopy, laser micro-Raman spectroscopy and liquid chromatography-electrospray ionization tandem mass spectrometry. The results showed that the yak meat redness value increased steadily relative to that of the control after the addition of low dose sodium nitrite. The nitrosomyoglobin level gradually increased and was significantly higher in the sodium nitrite-treated group than in the control group. The secondary structures were also transformed. The Cα-N bond extended and then contracted, the area of the haem core decreased and then increased and the frequency of contraction increased. A total of 34 nitrosylated peptides were identified, of which 15 were stable and 19 were unstable. These findings show that low doses of sodium nitrite facilitated the dynamic transformation of the myoglobin nitrosylated peptide fragment, which in turn preserved the colour of the meat.